Language and conflict in Northern Ireland and Canada : a silent war - Muller, Janet, 1957- (Palgrave studies in minority languages and communities., 2010)
Janet Muller presents a unique contribution to understanding the interaction between language policy and planning and modern conflict resolution. Against the backdrop of Quebec/Canada since the 1995 Quebec referendum on secession, she provides an insider account from the North of Ireland, assessing through these two examples the interplay of conflict and language policy in the protection and promotion of languages in minoritised circumstances. The author outlines recent language policy trends in Quebec/Canada and details the place occupied by the Irish language in Northern Irish peace negotiations prior to and after the 1998 Good Friday Agreement. She examines the extent to which promises of ₁a new era₂ for the language have been fulfilled and analyses development in language policy and planning through broadcasting, the implementation of the European Charter for Regional or Minority Languages and the aftermath of the 2006 British government commitment to enact an Irish language Act. New materials and interviews relevant to both Quebec/Canada and the North of Ireland provide fresh perspectives on some of the challenges facing minoritised language communities.